Pengaruh Pengungkapan Corporate Social Responsibility, Intellectual Capital, Ukuran Perusahaan Dan Peringkat Kinerja Lingkungan Terhadap Kinerja Keuangan - Hasanah, Neneng; Widiyati, Dian (Politeknik Raflesia Press, 2024)
— The purpose of this study was to examine the effect of Corporate Social Responsibility Disclosure, Intellectual Capital, Company Size, and Environmental Performance Ratings on Financial Performance. Indepnendent Variabel are Corporate Social Responsibility, Intellectual Capital, Company Size, and Environmental Performance Ratings, while the dependent variable is Financial Performance. The population in this study were mining company in the 2021-2023 period. The data collection technique used was purposive sampling, in order to obtain a sample of 12 companies with 36 data that match the criteria. The results of this study indicate that the variables of effect of Corporate Social Responsibility, Intellectual Capital, Company Size, and Environmental Performance Ratings do not have effect on financial performance (T Test). However, simultan test, tresults of this study are variabels do not have effect.